2011
DOI: 10.1038/nature10623
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 restriction factor SAMHD1 is a deoxynucleoside triphosphate triphosphohydrolase

Abstract: SAMHD1, an analogue of the murine interferon (IFN)-γ-induced gene Mg11 (ref. 1), has recently been identified as a human immunodeficiency virus-1 (HIV-1) restriction factor that blocks early-stage virus replication in dendritic and other myeloid cells and is the target of the lentiviral protein Vpx, which can relieve HIV-1 restriction. SAMHD1 is also associated with Aicardi-Goutières syndrome (AGS), an inflammatory encephalopathy characterized by chronic cerebrospinal fluid lymphocytosis and elevated levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
831
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 738 publications
(881 citation statements)
references
References 30 publications
31
831
4
3
Order By: Relevance
“…SAMHD1 is a dual-function enzyme with both nuclease and deoxyribonucleoside triphosphate triphosphohydrolase (dNTPase) activities (21,22). Germ-line mutations in SAMHD1 have been associated with Aicardi-Goutieres syndrome, a congenital autoimmune disease (23), and more recently SAMHD1 was shown to be an HIV-1 restriction factor operating in nondividing blood cells (24,25).…”
mentioning
confidence: 99%
“…SAMHD1 is a dual-function enzyme with both nuclease and deoxyribonucleoside triphosphate triphosphohydrolase (dNTPase) activities (21,22). Germ-line mutations in SAMHD1 have been associated with Aicardi-Goutieres syndrome, a congenital autoimmune disease (23), and more recently SAMHD1 was shown to be an HIV-1 restriction factor operating in nondividing blood cells (24,25).…”
mentioning
confidence: 99%
“…1 clearly demonstrates that the rNMP-mediated pausing disappears when HIV-1 RT synthesizes DNA at a fast rate with elevated dNTP concentrations. In fact, we and others recently reported that the limited dNTP pool found in macrophages is due to the expression of host restriction factor, SAMHD1, which is a dNTP triphosphohydrolase (5,45). Indeed, we also reported that HIV-2 and some SIVs encode an accessory protein, Vpx, that antagonizes the anti-viral function of SAMHD1 by proteasomal degradation.…”
Section: Discussionmentioning
confidence: 74%
“…During uptake, the virus binds the C‐type lectin DC‐SIGN, which triggers a tolerogenic immune response involving downregulation of specific immune signaling molecules that may help the virus evade early detection (Hodges et al , 2007; Shan et al , 2007). Within the cytosol, HIV‐1 encounters the deoxyribose nucleoside triphosphate hydrolase SAMHD1, which limits the efficiency of HIV reverse transcription and inhibits replication (Goldstone et al , 2011; Hrecka et al , 2011; Laguette et al , 2011). This prevents detection of reverse‐transcribed viral DNA and activation of interferon responses (Gao et al , 2013; Bridgeman et al , 2015; Gentili et al , 2015).…”
Section: Introductionmentioning
confidence: 99%